1989
DOI: 10.1104/pp.91.2.780
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Cadmium, Zinc, Cd-Peptide, and Organic Acid in Tobacco Suspension Cells

Abstract: Responses of tobacco (Nicotiana tabacum) suspension cells to Cd and Zn were studied in the presence and absence of ligand of Cd-peptide in order to understand the role of this peptide versus other mechanisms in Cd and Zn accumulation and accommodation in plants. With 45 micromolar Cd and 300 micromolar Zn (non-growth-inhibiting levels), metals appeared rapidly within cells, and intracellular Cd and Zn reached medium concentrations after 6 to 10 hours. Cd-peptide was observed in response to Cd after 2 hours, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
61
1
4

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 144 publications
(69 citation statements)
references
References 22 publications
3
61
1
4
Order By: Relevance
“…Earlier, Krotz et al (9) showed that after 3 to 4 d exposure of Datura cultured cells to 30 to 45 AM Cd most of the metal was recovered in isolated vacuoles. A number of studies using electron microscopy techniques have shown the presence of Cd deposits in vacuoles as well as other sites within tissues of plants exposed to high levels of Cd (5,19,25,26).…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…Earlier, Krotz et al (9) showed that after 3 to 4 d exposure of Datura cultured cells to 30 to 45 AM Cd most of the metal was recovered in isolated vacuoles. A number of studies using electron microscopy techniques have shown the presence of Cd deposits in vacuoles as well as other sites within tissues of plants exposed to high levels of Cd (5,19,25,26).…”
Section: Methodsmentioning
confidence: 97%
“…The study was carried out using a computer model, GEO-CHEM-PC (16,23), to simulate the chemical thermodynamic state of the vacuole based principally on chemical data of vacuole content of tobacco suspension cells (9). The GEO-CHEM-PC computer model uses an iterative procedure to solve simultaneously all equations describing dissolved and solid species.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations